Sistem Kontrol Robot Pengintai Berbasis Video Sender - Sakur Sakur; Achmad Ubaidillah (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2019)
The development of industrial technology has caused the transition of the use of human and animal power to be replaced by mechanical technology and robots. One of them is the fourth industrial revolution or industry 4.0 that occurred in 2012, industry 4.0 introduced the Cyber-Physical production process, this Industry 4.0 leads to an internet-based or wireless network manufacturing process, the use of this technology is not only limited to communication but also remote control that is quite far away. Therefore, it is a challenge for the nation's children who are already engaged in this technology, so researchers designed a tank-shaped surveillance device that can be controlled remotely which has several advantages, one of which is that it can be used in a dangerous place or place which is at high risk for humans when entering it, this robot can be controlled remotely using telemetry as its control and equipped with a monitoring camera or monitiring to complete the performance of the surveillance robot connected to the sender audio video module as the sender and receiver of audio video data displayed on the screen monitor, in carrying out the tasks of this robot is more flexible and also for the controller does not have to go directly to the location because the system has been controlled remotely so it does not take time and energy, and also the robot is equipped with a clamp or gripper that can take and put goods. The level of success in this design is 97.50%